Sunday Morning Market: Efforts to Increase Cadger's Income in Sharia Economic Perspective - ahmad bustomi; Isna Fitria Uswatun Kasanah; Lilis Renfiana (Jurnal Internasional Ekonomi Islam, 2022)
The economic increasing strategy of Cadger in Islamic Economy Perspective at Sunday Morning Market. Sultan Agung Stadium Sunday Morning Market is market in the Sunday morning which is the location in Sultan Agung Stadium in Bantul City. This market was founded on 2007. Since established, this market passesrapid development. This condition proved by the increasing of the number of Cadger and visitor. This research is descriptive qualitative research. The purpose of this research is to describe of Sunday morning management strategy and the result of economic increasing which is gotten by Cadger in Sunday Morning Market. Informan determination technique utilizes purpose sampling technique. Data collecting technique utilizes are observation, interview and documentation. All data seen the validity of data through tringaluation of source and data, and then analized by data reduction process, display data and conclution. The result of this research indicates that management strategy which utilized by team management of Sunday Morning market in Sultan Agung Stadiummakes regulation to Cadger registration, chose the retribution (cost for Cadger), selection for seller, information center, cleaning service, seller experiment, make a role for seller of Sunday Morning Sultan Agung Stadiummarket. Relocation about location determination and the increasing of people contribution into develop market of Sunday Morning Sultan Agung Stadium. Acoording those aspects, there are four strategyes which influencing the economy of Cadger, namely: location choice, inforrmation center, retribution and seller choice. All strategies are convenient with the axioms of Islamic economy, namely unity, equilibrium, free will and responsibility.